If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (6x + 8) Reorder the terms: x = (8 + 6x) Remove parenthesis around (8 + 6x) x = 8 + 6x Solving x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. x + -6x = 8 + 6x + -6x Combine like terms: x + -6x = -5x -5x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 -5x = 8 + 0 -5x = 8 Divide each side by '-5'. x = -1.6 Simplifying x = -1.6
| 3318.1008=2*33.24*r^2+2*3.13*r*36.5 | | w^2-6w-22=-25+w^2 | | 10+2k=18 | | 9k+2=13 | | 0=.01x^2+.7x+6.1 | | 3x+31.5=123 | | w/7+43=46 | | 2s-9=3 | | w^2-6w-22=-25w^2 | | 2(-4+7x)=6x-6+30 | | X+20+2x-5=50 | | 2s-1=1 | | 3y-30=2x | | 2(2y+2)+3y=19 | | 2d+6=16 | | -x+10=-x+14 | | x=(7x+6) | | 3f-3=6 | | 36=9+9s | | (-.01x^2)+.7x+6.1=y | | 24(6)+4x=180 | | y=7x+13forx | | x^2+0.25=1.25 | | Y=-2x^2+12x-3 | | 2(4x+8)=7x+6+14 | | r^2-19r=-7r+64 | | 6x-7+4x+23=45 | | 6x-7+4x+23=10 | | abs(z+2i)+abs(z-2i)=6 | | -4(x+8)=-8x-20 | | (5x-4)(5x-4)=16 | | 4-3x=7(x-7) |